2008
DOI: 10.1177/1934578x0800300605
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Ximenia Americana

Abstract: Two steroids (1 and 2), five pentacyclic triperpenoids (3-7) and a new furanosesquiterpene (8) were isolated from the stems of Ximenia americana, family Olacaceae. The structures of the compounds were established by spectral data; two-dimensional NMR spectroscopy has been used to assign all 1 H and 13 C chemical shifts of 8. Compound 8 did not inhibit the growth of HL-60 (human leukemia), HTC-8 (human colon), and MDA-MB-435 (human breast cancer) cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…2019) characterized the chromatographic profile (by high-performance liquid chromatography-HPLC) of the same extract, revealing the presence of the compounds quercitrin and caffeic acid as major components, in addition to several others, such as quercetin, rutin, gallic acid, catechin, chlorogenic acid, ellagic acid, and kaempferol [31,32]. A similar chemical composition was observed in other studies, indicating low chemical variation among the samples [14,15].…”
Section: Inhibition Of Gastrointestinal Motility By Ehxa and Atropinesupporting
confidence: 57%
See 4 more Smart Citations
“…2019) characterized the chromatographic profile (by high-performance liquid chromatography-HPLC) of the same extract, revealing the presence of the compounds quercitrin and caffeic acid as major components, in addition to several others, such as quercetin, rutin, gallic acid, catechin, chlorogenic acid, ellagic acid, and kaempferol [31,32]. A similar chemical composition was observed in other studies, indicating low chemical variation among the samples [14,15].…”
Section: Inhibition Of Gastrointestinal Motility By Ehxa and Atropinesupporting
confidence: 57%
“…The chemical composition of the ethanolic extract of X. americana bark (EHXA) was determined using qualitative and quantitative analyses. Qualitative analysis revealed the presence of various metabolite classes, including phenols, anthocyanins, anthocyanidins, flavonols, chalcones, aurones, leucoanthocyanidin, catechins, and steroids [15,31]. In previous research, our group reported the quantitative chemical profile of polyphenols in EHXA using the HPLC-DAD method, which identified significant compounds such as caffeic acid and quercitrin, as well as other phenolic derivatives, including gallic acid, chlorogenic acid, ellagic acid, and flavonoids such as catechin, rutin, quercetin, and kaempferol [31,32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations